P-Hydroxyacetophenone Ameliorates Alcohol-Induced Steatosis and Oxidative Stress via the NF-κB Signaling Pathway in Zebrafish and Hepatocytes - Huang, Sha; Zhou, Chuying; Zeng, Ting; Li, Yujia; Lai, Yuqi; Mo, Chan; Chen, Yuyao; Huang, Shaohui; Lv, Zhiping; Gao, Lei (Frontiers in Pharmacology, 2020)
Alcoholic liver disease (ALD), which is recognized as an important health problem worldwide, is a direct consequence of alcohol consumption, which can induce alcoholic fatty liver, alcoholic steatohepatitis, fibrosis and cirrhosis. P-Hydroxyacetophenone (p-HAP) is mainly used as a choleretic and hepatoprotective compound and has anti-hepatitis B, antioxidative and anti-inflammatory effects. However, no experimental report has focused on p-HAP in ALD, and the effect and mechanism of p-HAP in ALD remain unknown. In addition, there is no research on p-HAP in the treatment of ALD. The potential molecular mechanisms of p-HAP against acute alcoholic liver injury remain unknown. In this study, we aimed to investigate whether p-HAP alleviates ALD and to clarify the potential molecular mechanisms. Zebrafish larvae were soaked in 350 mmol/l ethanol for 32 h at 4 days post fertilization (dpf) and then treated with p-HAP for 48 h. We chose various outcome measures, such as liver histomorphological changes, antioxidation and antiapoptosis capability and expression of inflammation-related proteins, to elucidate the essential mechanism of p-HAP in the treatment of alcohol-induced liver damage. Subsequently, we applied pathological hematoxylin and eosin (H&E) staining, Nile red staining and oil red O staining to detect the histomorphological and lipid changes in liver tissues. We also used TUNEL staining, immunochemistry and Western blot analysis to reveal the changes in apoptosis- and inflammation-related proteins. In particular, we used a variety of fluorescent probes to detect the antioxidant capacity of p-HAP in live zebrafish larvae in vivo. In addition, we discovered that p-HAP treatment relieved alcoholic hepatic steatosis in a dose-dependent manner and that the 50 μM dose had the best therapeutic effect. Generally, this research indicated that p-HAP might reduce oxidative stress and cell apoptosis in vivo and in vitro via the NF-κB signaling pathway.